'Musical effort' and 'musical pleasantness': a pilot study on the neurophysiological correlates of classical music listening in adults normal hearing and unilateral cochlear implant users. (3rd April 2022) - Inguscio, Bianca Maria Serena; Mancini, Patrizia; Greco, Antonio; Nicastri, Maria; Giallini, Ilaria; Leone, Carlo Antonio; Grassia, Rosa; Di Nardo, Walter; Di Cesare, Tiziana; Rossi, Federica; Canale, Andrea; Albera, Andrea; et al.
Abstract: Objective: This pilot case-control study is aimed to estimate 'musical effort' and 'musical pleasantness' in adults normal hearing (NH) and Unilateral Cochlear Implant (UCI) users via neurophysiological indices and a cognitive-behavioural approach. Methods: 7 NH and 7 UCI subjects underwent electroencephalographic (EEG) recording with two EEG indices, Approach Withdrawal (AW) and Workload (WI), and behavioural tests conducted during a forced-choice musical emotion recognition task performed in quiet and noise in two emotional conditions. Results: Musical effort in terms of WI did not vary between conditions and groups. Inversely, for AW, statistically significant differences in noisy conditions were observed between groups, indicating a difficulty for the patients in discriminating the musical pleasantness in noise. However, self-reported data suggest the ability of UCI to cognitively evaluate the stimulus in terms of both auditory difficulty and pleasantness. Conclusion: Findings suggest the possible relevance of the Cochlear Implant in supporting the patients' effort in listening to music in noise, allowing a pleasant enjoyment in the quiet condition. Overall, this study appears worthy of interest and paves the way for further investigation by providing data on the neurophysiological perception of music.